Patient-derived monoclonal myelin oligodendrocyte glycoprotein autoantibodies mediate cytotoxicity - Wetzel, Nora; Kulsvehagen, Laila; Lecourt, Anne-Catherine; Filipek, Beata; Lipps, Patrick; Rieder, Laura; Berve, Kristina; Krishnamoorthy, Gurumoorthy; 't Hart, Bert A.; Schirmer, Lucas; Yandamuri, Soumya S.; O'Connor, Kevin C.; et al. (Neurology: Neuroimmunology & Neuroinflammation ; official journal of the American Academy of Neurology, 2026)
Background and Objectives - Serum myelin oligodendrocyte glycoprotein (MOG) antibodies are a hallmark of the newly defined neuroinflammatory disease entity MOG antibody-associated disease (MOGAD). Yet, the lack of patient-derived recombinant human MOG (hMOG)-reactive autoantibodies limits investigations into the molecular mechanisms by which these autoantibodies mediate CNS pathology, thereby hindering rational therapeutic approaches. To understand the origins and disease-relevant mechanisms of autoantibodies in MOGAD, we generated and characterized monoclonal anti-hMOG antibodies (MOG-mAbs) from circulating B cells of patients with MOGAD. - Methods - We isolated MOG-specific B-cell receptor (BCR) sequences from unique circulating B-cell clones of 6 patients with MOGAD using an antigen selection approach. BCR sequences were expressed as immunoglobulin (Ig)G1 antibodies, and their molecular features, epitope specificity, and binding to MOG isoforms were investigated. The MOG-mAbs’ ability to mediate antibody-dependent cellular phagocytosis (ADCP), natural killer (NK) cell-mediated antibody-dependent cellular cytotoxicity (ADCC), and complement-dependent cytotoxicity (CDC) toward MOG-expressing cells was assessed by live cell-based assays. - Results - Of the 15 MOG-mAbs generated, 4 revealed evidence of affinity maturation, whereas the remaining 11 were germline encoded. Binding capacities to hMOG varied considerably, with the most frequent putative epitope mapping to a region that includes residue P42. The efficacy of these antibodies in mediating ADCP, ADCC, and CDC of MOG-expressing cells was heterogeneous and associated with their binding characteristics to MOG and its isoforms. - Discussion - Taken together, the molecular characteristics and binding patterns of these patient-derived MOG-mAbs reveal a diverse repertoire of MOG-binding autoantibodies with pathogenic capacity in vitro. Consequently, these well-characterized patient autoantibodies offer a foundation for developing in vivo models of MOGAD, serve as tools to standardize diagnostic assays, and guide development of therapeutic strategies targeting either B cells or autoantibodies and their effector functions.
Online veröffentlicht: 17. Dezember 2025
Gesehen am 18.02.2026